A STUDY ON THE INFLUENCING FACTORS OF ONLINE SHOPPING AND PURCHASING DECISIONS AMONG COLLEGE STUDENTS: AN EMPIRICAL STUDY - Jain Jacob M, Dr. M. Shanmugam (International Journal of Advanced Science and Technology, 2020)
The population of online shoppers is increasing unpredictable in current Indian scenario. The popularity of online shopping among teenagers is gaining its pace because of several factors which influence their purchasing decisions. The present study intended to analyze and find out the influencing factors of online shopping and purchasing decisions among college students with special reference to students of St. Dominic’s Arts and Science College, Kanjirapally, Kerala State. Adequate samples have been collected using systematic random sampling technique. The study concluded that availability of new trendy fashion apparels; introduction of new technology gargets and finally the urge to purchase them popularize online shops among college students and youngsters.  By identifying these factors, e-business companies can improve their business by act according to the needs and wants of customers.